Utilização de resíduos da indústria galvanotécnica no desenvolvimento e fabricação de blocos de concreto para pavimentação intertravada - Sgorlon, Juliana Guerra (2014)
The present work aimed to study the treatment/recycling of solid waste from the electroplating industry in the manufacture of concrete paving blocks, using the technique of stabilization/solidification in cement. Concrete blocks with different residues (blasting dust and galvanic sludge) (2%, 3%, 4%, 5% and 10%) in the substitution of fine aggregate were prepared. The blocks were subjected to physical, chemical, mechanical and microstructural tests for the assessment required to ensure good quality of the blocks, as for ensuring efficient removal/immobilization of contaminants in waste. The results obtained showed that the replacement of fine aggregate by up to 5% of blasting dust and 4% of galvanic sludge did not result in significant losses in the mechanical strength of the parts, nor lead to increased water absorption by the blocks. It has been found by chemical tests, there will be no problems of solubilization or leaching of contaminants during the useful life of the concrete blocks, since the process of solidification/stabilization leaded to physical and chemical immobilization of waste in cement mass. Thus, the use of blasting dust and electroplating sludge in manufacturing concrete paving blocks was feasible and effective, not only presenting itself as an alternative for the recycling and proper waste treatment, but also as a possibility of raw materials economy in the construction business.